Nurturing Trade for Better Indian Economy - Tiwari, Munish Kumar (Journal of Commerce and Trade, 2012)
Trade has a vital role to play in helping developing countries to boost their economic growth and to generate the resources necessary for reducing poverty. In the 1950s and 1960s, protectionist policies in developing countries – promoting industrialization by restricting imports of manufactures – were often associated with quite rapid growth.Getting a predevelopment position across this wide range of trade issues is of enormous importance in securing a fairer deal for poor countries from international trade and in a future multilateral Trade Round. The Government continues to push for the bilateral free trade agreements to be consistent with our wider development goals. However, many products are excluded from the scheme, and it is difficult and complex to use.